Eksplorasi kemampuan penalaran dan representasi matematis siswa sekolah menengah pertama - Absorin, Absorin; Sugiman, Sugiman (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2018)
Penelitian ini bertujuan untuk mendeskripsikan kemampuan matematis, yang terdiri atas kemampuan penalaran dan representasi matematis siswa SMP di Kabupaten Indramayu, Jawa Barat. Penelitian ini merupakan penelitian survei dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah seluruh siswa SMP kelas VIII di Kabupaten Indramayu tahun pelajaran 2016/2017. Sampel penelitian sebanyak 390 siswa. Teknik pengambilan sampel yang digunakan adalah stratified random sampling.Pengumpulan data dilakukan melalui teknik Tes. Teknik analisis data menggunakan statistika deskriptif melalui dua cara, yaitu estimasi titik dan estimasi interval rata-rata untuk menentukan kategori ketercapaian pada masing-masing kemampuan matematis siswa. Hasil penelitian menunjukkan bahwa kemampuan matematis siswa SMP di Kabupaten Indramayu berada pada kategori sedang. Secara lebih spesifik rata-rata skor pada kemampuan penalaran matematis siswa termasuk dalam kategori sedang. Begitu juga pada rata-rata skor kemampuan representasi matematis siswa berada pada kategori sedang. Exploration ability of mathematical reasoning and representation of junior high school students AbstractThis study aimed to describe the mathematical ability, which consists of the ability of mathematical reasoning and representation in junior high school students in Indramayu, West Java Province, Indonesia. This research was using survey method with quantitative approach. The population in this study were all grade VIII students in both state and private junior high schools in Indramayu district in academic year of 2016/2017 and 390 students selected as sample research. The sampling technique was stratified random sampling. Data collected using test technique. Technique data analysis used descriptive statistics through two ways, namely estimation point and the average of interval estimation to determine the category of achievement in each of the students' mathematical abilities. The result showed that the mathematical ability of junior high school students in Indramayu district was in the medium category. More specifically the average score on students' mathematical reasoning abilities was included in the moderate category. Similarly, the average score of students' mathematical representation ability was in the medium category.